Menelusuri Makna Mantuq, Mafhum, Zahir dan Muawwal Dalam Hukum Islam - Hidayatulah Abdul Rachman; Imam Sucipto; Mida Hardianti (Cakrawala: Journal of Religious Studies and Global Society, 2025)
The understanding of linguistic principles such as mantuq, mafhum, zhahir, and muawwal is a fundamental foundation for interpreting Qur'anic verses and Hadith accurately and in alignment with contemporary needs. This study systematically explores these concepts by integrating classical and contemporary sources while providing examples of their application in modern contexts. By employing a qualitative approach and descriptive-analytical methods, this research not only offers in-depth explanations but also presents solutions to the challenges of applying these principles in multicultural societies. The findings of this study mark a significant step in maintaining the relevance of Islamic law, bridging textual wisdom with values of public benefit oriented towards a dynamic modern life.